Eksplorasi Trends dalam Work Engagement dan Work Family Conflict dengan Metode Bibliometrik - Ciptagustia, Annisa; Kusnendi, Kusnendi; Perdana, Yoga; Faldesiani, Riske (Universitas Pendidikan Indonesia, 2023)
The purpose of the study is a comprehensive picture of work engagement and work family conflict for the criteria of key authors, documents, and keywords and mapping the development of research through a bibliometric approach with computational mapping analysis using VOSviewer. This research used bibliometric analisis with VOSviewer sofware. This study used the Scopus database using A comma separated value (CSV) format consisting of 440 reference metadata used for analysis in VOSviewer in the period 1993-2023. Clustering of the network visualisation map was done using 2 keywords, namely, work engagement and work family conflict. The analysis showed that most of the publications were done in 2022 with 69 articles with a high number of citations in this field from researchers in the United States and China. A total of 11 articles were published in the International Journal Of Environmental Research And Public Health and the documents referenced or heavily cited came from the Journal Of Occupational And Environmental Medicine with 469 articles.